Comparison in Efficacy of Misoprostol and uterine- Foley- Balloon Tamponade in Postpartum Haemorrhage - Qamar, Shanza; Hanif, Sadia; Afraz, Negah; Khadim, Madiha; Shamraiz, Kashaf; Sabir, Maryam (Indus Journal of Bioscience Research, 2025)
Background: Postpartum hemorrhage remains one of the leading causes of maternal morbidity and mortality, especially in low-resource settings. Misoprostol and uterine Foley balloon tamponade are widely used therapeutic approaches, but limited data exist from Azad Kashmir regarding their comparative effectiveness. Objective: To compare the efficacy of misoprostol versus uterine Foley balloon tamponade among pregnant women in management of post-partum haemorrhage. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted at the Department of Obstetrics and Gynecology, CMH Rawalakot, from December 2024 to May 2025. Methodology: A total of 206 women aged 18–45 years presenting with primary PPH were enrolled and randomly assigned to two equal groups. Group A received 1000 µg misoprostol per rectum, while Group B was managed with uterine Foley balloon tamponade. Demographic and clinical data, including parity, gestational age, blood loss, delivery type, and neonatal weight, were recorded. Treatment was considered successful if bleeding was controlled without further complications. Results: The mean age of participants was 33.41±7.50 years in the misoprostol group and 30.86±7.79 years in the Foley balloon group. Misoprostol achieved efficacy in 88.3% of patients, while the Foley balloon was effective in 81.6% (p=0.173). Conclusion: Both misoprostol and uterine Foley balloon tamponade demonstrated comparable efficacy in controlling PPH, making them viable options in resource-constrained clinical environments.